Manganese halide hybrids with a reversible luminous color and their application for a white light-emitting diode. Issue 39 (21st September 2022) - Fu, Hanmei; Jiang, Chunli; Luo, Chunhua; Lin, Hechun; Peng, Hui
Abstract : Two manganese halide hybrids, (C5 H8 N2 )2 MnCl4 and C5 H8 N2 (MnCl2 ) x Cl y, with reversible luminous colors and their application for a white light-emitting diode. Abstract : Organic–inorganic manganese halide hybrids have attracted attention in the field of light-emitting diodes (LEDs) due to their simple preparation, environmental friendliness and tunable luminescence. Herein, two manganese halide hybrids, (C5 H8 N2 )2 MnCl4 and C5 H8 N2 (MnCl2 ) x Cl y, are synthesized by adopting different ratios of 1-ethylimidazole and MnCl2 . (C5 H8 N2 )2 MnCl4 and C5 H8 N2 (MnCl2 ) x Cl y show strong green and red emission with photoluminescence quantum yields (PLQYs) of up to 79.77% and 83.33%, respectively, which is attributed to the different coordination environments of Mn 2+ . The reversible conversion between red and green emission of C5 H8 N2 (MnCl2 ) x Cl y coming from its decomposition and recovery makes it an interesting fluorescent material. Their applications in fabrication of a white LED (WLED) and a tunable color LED by combining with a blue GaN LED illustrate their great potential as effective phosphors for solid-state light-emission.